Aktivitas Antagonistik Jamur yang Berasosiasi dengan Nematoda Bengkak Akar (Meloidogyne spp.) pada Rizosfer Tanaman Tomat: English - Winarto, Winarto; Trizelia, Trizelia; Liswarni, Yenny (Jurnal Proteksi Tanaman (Journal of Plant Protection), 2018)
The purpose of experiment were to know antagonistic activity of fungi to root-knot nematode (Meloidogyne spp.) in rhizosphere of tomato. The experiment consisted of isolation, test of antagonistic activity and identification of fungi that carried out at Phytopathology Laboratory of Universitas Andalas. Soil samples were taken from rhizosphere of healthy tomato in Alahan Panjang, Solok, and Agam. The results indicated that there were seven antagonistic fungi to Meloidogyne spp., namely: Paecilomyces sp., Penicillium, sp., Aspergillus sp., Fusarium sp., Gliocladium sp. Trichoderma sp., and Chaetomium sp.